Reviewing the reservation policy : in changing social order - Barik, Radhakanta (Delhi : Shipra Publications, 2012)
Papers presented at a two-day national seminar
Includes bibliographical references and index
Keywords: People with social disabilities -- Government policy -- India; People with social disabilities -- Education (Higher) -- India